Secure Key Exchange Against Man-in-the-Middle Attack: Modified Diffie-Hellman Protocol - Mostefa Kara; Abdelkader Laouid; Muath AlShaikh; Mohammad Hammoudeh; Ahcène Bounceur (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
One of the most famous key exchange protocols is Diffie-Hellman Protocol (DHP) which is a widely used technique on which key exchange systems around the world depend. This protocol is simple and uncomplicated, and its robustness is based on the Discrete Logarithm Problem (DLP). Despite this, he is considered weak against the man-in-the-middle attack. This article presents a completely different version of the DHP protocol. The proposed version is based on two verification stages. In the first step, we check if the pseudo-random value Î± that Alice sends to Bob has been manipulated! In the second step, we make sure that the random value Î² that Bob sends to Alice is not manipulated. The man-in-the-middle attacker Eve can impersonate neither Alice nor Bob, manipulate their exchanged values, or discover the secret encryption key.